Penggunaan Gadget dengan Perkembangan Mental Emosional Pada Anak Usia Prasekolah - Linda Ishariani (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
The use of gadgets in children can have positive and negative effects on children, especially in preschoolers. The negative impact of using gadgets is one of them emotional mental development. The purpose of this study was to determine the relationship between the use of gadgets and emotional mental development in preschool children. The design of this study is correlational with the population of mothers who have preschool-aged children and a sample of 35 respondents with purposive sampling technique. Data were collected by questionnaire and analyzed by Spearman's rho correlation. The results showed that most respondents used gadgets in the moderate category (60%), 85.77% experienced mental emotional development disorders. Spearman rho test results obtained p = 0.00 (p <α), there is a relationship between the use of gadgets with emotional mental development of preschool children. This is influenced by work, parenting and the role of parents. The role of teachers and parents is very important in preventing emotional mental disorders in children due to the use of gadgets.